RANCANG BANGUN SISTEM NOMER ANTRIAN BERBASIS INTERNET OF THINGS (IOT) - Wijaya, I Made Agus Chandra; Slamet Winardi (STMIK Palangkaraya, 2022)
Queuing is a phenomenon that we can encounter anywhere and anytime, such as queuing to get food orders, ticketing services, and so on. However, unfortunately not everyone likes to queue, especially queuing for public agency services. This is because of various kinds, such as irregular queues, the number of people queuing so that it makes people lazy to queue, or even because there is a sudden need so they cannot queue for long. Especially during the Covid-19 pandemic, people avoid physical contact between each other, so to overcome this, an organized queue number system is needed and can be ordered online through an application on a smartphone. Customers can order a queue number and monitor the queue number being served through an application on a smartphone, there is also a call to each queue number to be served. This research also applies the internet of things (IoT) system which is used to display the queue number served on a P10 LED Display.